2020
DOI: 10.3389/fimmu.2020.00253
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dietary Components on Regulatory T Cells and Disease

Abstract: The rise in the prevalence of autoimmune diseases in developed societies has been associated with a change in lifestyle patterns. Among other factors, increased consumption of certain dietary components, such as table salt and fatty acids and excessive caloric intake has been associated with defective immunological tolerance. Dietary nutrients have shown to modulate the immune response by a direct effect on the function of immune cells or, indirectly, by acting on the microbiome of the gastrointestinal tract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 194 publications
(225 reference statements)
0
23
0
Order By: Relevance
“…In the intestine, these bacteria have important immunoregulatory properties, as they provide a large variety of harmless antigens that continuously stimulate intestinal immune cells to be tolerant, not only to molecules produced by commensal bacteria, but also to exogenous proteins derived from food (Chistiakov et al, 2015). Moreover, microbiota derived signals have a direct impact on T cell differentiation, with some favoring the regulatory T cell subset, which is vital for the maintenance of the intestinal homeostasis (Arroyo Hornero et al, 2020).…”
Section: Dietary Effects In Food Allergy Incidence-microbiota Rolementioning
confidence: 99%
“…In the intestine, these bacteria have important immunoregulatory properties, as they provide a large variety of harmless antigens that continuously stimulate intestinal immune cells to be tolerant, not only to molecules produced by commensal bacteria, but also to exogenous proteins derived from food (Chistiakov et al, 2015). Moreover, microbiota derived signals have a direct impact on T cell differentiation, with some favoring the regulatory T cell subset, which is vital for the maintenance of the intestinal homeostasis (Arroyo Hornero et al, 2020).…”
Section: Dietary Effects In Food Allergy Incidence-microbiota Rolementioning
confidence: 99%
“…It is highly possible that regulatory mechanisms are deformed. It has been reported that nutritional factors can modulate Treg plasticity, metabolism, and function [ 54 ], even though we did not test for Tregs and anti-inflammatory responses, as our study focused on innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this SLE population, the most common triggers identified as correlating negatively with symptoms and leading to improvement upon elimination were all dietary—the top 3 being dairy, gluten, and nightshades. While these findings do not provide conclusive evidence linking dairy, gluten, and nightshades to SLE, accumulating data from in vitro, animal, and human studies support the need for ongoing investigation into these potential triggers [ 41 - 43 ].…”
Section: Discussionmentioning
confidence: 99%